2018
DOI: 10.1007/s11242-018-1105-3
|View full text |Cite
|
Sign up to set email alerts
|

Flow of a Cross-Linking Polymer in Porous Media

Abstract: Heterogeneous reservoirs often have poor sweep efficiency during flooding. Although polymer flooding can be used to improve the recovery, in-depth diversion might provide a more economical alternative. Most of the in-depth diversion techniques are based on the propagation of a system that forms a gel in the reservoir. Premature cross-linking of the system prevents the fluid from penetrating deeply into the reservoir and as such reduces the efficiency of the treatment. We studied the effect of using a polyelect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…Mohtar et al [22] studied the post-grouting stability of bentonite in porous media and established the relationship between the yield stress of the bentonite suspension and the critical water conductivity. Bedrikovetskya et al [23] and Lenchenkov et al [24] studied the flow of colloids in water and porous media, and confirmed the validity of their proposed model, which can also be used to predict potential well plugging. Civan and Vafai [25] examined the characteristic features of the fundamental flow mechanisms and discussed the essential parameters of relevant modeling approaches for the transportation of gas through dense, porous media.…”
Section: Introductionmentioning
confidence: 81%
“…Mohtar et al [22] studied the post-grouting stability of bentonite in porous media and established the relationship between the yield stress of the bentonite suspension and the critical water conductivity. Bedrikovetskya et al [23] and Lenchenkov et al [24] studied the flow of colloids in water and porous media, and confirmed the validity of their proposed model, which can also be used to predict potential well plugging. Civan and Vafai [25] examined the characteristic features of the fundamental flow mechanisms and discussed the essential parameters of relevant modeling approaches for the transportation of gas through dense, porous media.…”
Section: Introductionmentioning
confidence: 81%
“…Field tests show that in-depth profile control can effectively block fractures and high-permeability reservoirs [19,20], and it can cause subsequently displaced fluid to flow into lowpermeability reservoirs to displace residual oil [21]. Nevertheless, in-depth profile control techniques have many problems, such as short-term validity, decreased effects of enhanced oil recovery, and scale formation from the reaction between bicarbonate radical ions in weak gels and calcium ions in strata [22]. Therefore, the enhanced oil recovery of in-depth profile control is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Many scholars have studied the mechanism of crosslinked polymer flooding (Shriwal and Lane, 2012;Brattekas et al, 2015;Lenchenkov et al, 2018). Himes et al (1994) developed a new, environmentally friendly polymer for the well completion and stimulation treatments where a premium is placed on maximizing effectiveness while minimizing formation damage.…”
Section: Introductionmentioning
confidence: 99%